Comparison Of Financial Distress In Companies Affected By The Covid-19 Pandemic (Empirical Study Of Hotel, Restaurant, Tourism, And Aviation Sub Sector Companies Listed On The Indonesia Stock Exchange) - Nikmah, Siska Khoirun; Bhilawa, Loggar; Harun, Harun (International Economic Conference of Business and Accounting, 2024)
The extraordinary impact on the global economy in early 2020 was caused by COVID-19, one of which was financial system stability. Economic instability causes a decrease in company revenue, especially in hotel, restaurant, tourism and aviation subsectors, which can lead to financial distress. Financial Distress analysis is important to provide an overview of the company’s financial condition. This study aims to determine the difference in the level of financial distress before and during the COVID-19 pandemic in hotel, restaurant, tourism, and aviation sub-sector companies listed on the Indonesia Stock Exchange (IDX) in 2019–2022, using the Altman Z-score calculation model. The data used in this study are secondary data taken from financial reports through the official IDX website, www.idx.co.id. Sample determination was carried out using the purposive sampling method. The number of samples selected was 36 companies. The analysis technique used in this research is one-way analysis of variance. The results showed a value of 0.885 > 0.05, which means that there is no difference in the level of financial distress in companies before and during the COVID-19 pandemic.The extraordinary impact on the global economy in early 2020 was caused by COVID-19, one of which was financial system stability. Economic instability causes a decrease in company revenue, especially in hotel, restaurant, tourism and aviation subsectors, which can lead to financial distress. Financial Distress analysis is important to provide an overview of the company’s financial condition. This study aims to determine the difference in the level of financial distress before and during the COVID-19 pandemic in hotel, restaurant, tourism, and aviation sub-sector companies listed on the Indonesia Stock Exchange (IDX) in 2019–2022, using the Altman Z-score calculation model. The data used in this study are secondary data taken from financial reports through the official IDX website, www.idx.co.id. Sample determination was carried out using the purposive sampling method. The number of samples selected was 36 companies. The analysis technique used in this research is one-way analysis of variance. The results showed a value of 0.885 > 0.05, which means that there is no difference in the level of financial distress in companies before and during the COVID-19 pandemic.